Teaching and Learning Continuity Amid and Beyond the Pandemic - Dayagbil, Filomena T.; Palompon, Daisy R.; Garcia, Laurence L.; Olvido, Michelle Mae J. (Frontiers in Education, 2021)
The study explored the challenges and issues in teaching and learning continuity of public higher education in the Philippines as a result of the COVID-19 pandemic. The study employed the exploratory mixed-method triangulation design and analyzed the data gathered from 3, 989 respondents composed of students and faculty members. It was found out that during school lockdowns, the teachers made adjustments in teaching and learning designs guided by the policies implemented by the institution. Most of the students had difficulty complying with the learning activities and requirements due to limited or no internet connectivity. Emerging themes were identified from the qualitative responses to include the trajectory for flexible learning delivery, the role of technology, the teaching and learning environment, and the prioritization of safety and security. Scenario analysis provided the contextual basis for strategic actions amid and beyond the pandemic. To ensure teaching and learning continuity, it is concluded that higher education institutions have to migrate to flexible teaching and learning modality recalibrate the curriculum, capacitate the faculty, upgrade the infrastructure, implement a strategic plan and assess all aspects of the plan.